Tax policy impact on shadow economy - A. S. Yakovleva; E. G. Lyubovtseva (Вестник университета)
The article examines the relationship between tax policy and the shadow economy. The tax burden was chosen as a tax policy indicator; the shadow economy is assessed using the Rosstat methodology. When comparing the tax burden in the country as a whole and the shadow economy volumes, a decrease in the shadow economy indicators was noted with a relatively high tax burden. When comparing the shadow economy and the tax burden by economic activity types, an insignificant relationship between the studied indicators was revealed, however, in some sectors of the economy, a feedback was noted. The introduction of a tax on professional income has led to an increase in the number of self-employed. However, the share of the self-employed in the number of those employed in the informal sector in the Volga Federal District showed a high heterogeneity across regions. The conclusion was drawn about the influence of many factors on the shadow economy, as a result of which the use of only fiscal policy instruments to reduce the shadow sector seems insufficient.